The Possibility of Converting Available Spaces into Pocket Parks in Urban Settlements in Indonesia - Shirleyana, Shirleyana (e-Jurnal Eco-Teknologi UWIKA (eJETU), 2013)
In highly dense settlement, particularly in the city center, land is very expensive. Large scale development happened and there are growing needs to improve the urban environment with green spaces to improve the qualityof life for the city inhabitants. One alternative to provide green open space for the community is converting limited available space into pocket park. In many cases, pocket parks have played different roles: green space, ecological park, and also community gathering space. Pocket parks are the only option to create public spaces to improve the quality of life without major changes in the environment. This study would like to evaluate the possibility of creating pocket parks in highly dense settlement area in Indonesia with community participation. Thus it is no longer impossible to create green space within limited space.Keyword: pocket park, green space, highly dense settlement, community participation.